Peran Dinas Sosial dan Tenaga Kerja Kabupaten Sidoarjo dalam Pemberdayaan Anak Jalanan di Kecamatan Sidoarjo - Sane'a Sane'a; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2014)
The aims of this research were to describe the role of Social and Labor Department in empowering homeless children in Sidoarjo Subdistrict and to know the type of the empowering that has been done by Social and Labor Department in reducing the number of homeless children. The research method in this study used qualitative with descriptive approach. Based on research result, it is known Social and Labor Department Sidoarjo Regency has big role in empowering homeless children in Sidoarjo Subdistrict. However, there were causing factors that increased the number of homeless children. It was attitude of homeless children which is free life and they were difficult to be handled. Consequently, Social and Labor Department Sidoarjo Regency has strategy to handle homeless children that is by giving religion and moral guidance; increasing the training, developing and creativity of homeless children; developing for parents and health; and also cooperating with involved SKPD such as P2TP2A, BPMPKB, Bappeda, Education Department. This strategy was done in attempt of giving provisions to homeless children so that they will be able to interact better in society which appropriate with courtesy norm, this condition is the opposite with their condition before the developing and training is done.